Web-based Application Forecasting of Components and Tools for Practicum in Telecommunication Engineering Laboratory/ Workshop of State Polytechnic of Sriwijaya - Elmerillia, Elmerillia; Lindawati, Lindawati; Salamah, Irma (ELKHA : Jurnal Teknik Elektro, 2021)
State Polytechnic of Sriwijaya is an Indonesian vocational institution that incorporates practical learning into all of its existing study programs. In each laboratory of the study program, students will find the supporting components and resources they need for practicum. Telecommunication engineering is one of them. Currently, the component retrieval and tool borrowing system is still manual, both in the retrieval and return stages, by filling out the given hard-file form sheet. Therefore, a web-based inventory monitoring application is required for laboratory technicians. The creation of this application implements the Prototype Method. The implementation of this method aims to make the application that is created to fit the needs of the user. This system helps laboratory technicians and Telecommunication Engineering students in the process of component retrieval and tool borrowing to be more organized and scheduled and can store reports in the form of soft-files. This information system can also be used by students to monitor the number of components and tools available in real-time. This application are also equipped with forecasting the number of practicum components to kwowing the needs of student practicum in the next year. Forecasting was created using the Weighted Moving Average method.Â  Black box testing is carried out in each menu on the application and gives valid results so that the application can be used.Â